2019
DOI: 10.3390/nu11092045
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Burden of Iron Deficiency Anemia in France from Iron Intake: Methodological Approach

Abstract: Dietary iron deficiency (ID) is the first nutritional deficiency in the world, in terms of disability adjusted life years (DALY). This nutritional deficiency may lead to anemia, especially among children, adolescents, and adult women. The aim of this study was to build an original probabilistic model to quantitatively assess the ID, the iron deficiency anemia (IDA) and the subsequent health burden in France expressed in DALY, per age class and gender. The model considered the distribution of absorbed iron inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
1
6
0
2
Order By: Relevance
“…Overall, the prevalence of ID and IDA were significantly higher in females compared to males (3)(11)(13)(14)(17)(25)(26). One study concluded that there are, however, differences in the risk factors even among reproductive aged women by successfully identifying several significant risk factors in the older population (22-49 years) but not finding any variables for predicting IDA in the younger study population (12-21 years) (23).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Overall, the prevalence of ID and IDA were significantly higher in females compared to males (3)(11)(13)(14)(17)(25)(26). One study concluded that there are, however, differences in the risk factors even among reproductive aged women by successfully identifying several significant risk factors in the older population (22-49 years) but not finding any variables for predicting IDA in the younger study population (12-21 years) (23).…”
Section: Resultsmentioning
confidence: 97%
“…One of the studies found ID prevalence to be the highest in the younger age group and decreasing with age(17). For females prevalence of both ID and IDA was significantly higher in reproductive age compared to older age groups (3)(13)(16)(17)(21)(22).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A prevalência da anemia entre adolescentes do sexo feminino é também descrita em estudos internacionais de base populacional, a exemplo do ENSANUT MC 2016, cuja prevalência em adolescentes de ambos os sexos foi de 9,6% [IC95% 7,8,11,8] e no sexo feminino de 12% (De la Cruz-Góngora, 2018). Urrechaga et al, [2016] seja devido ao consumo insuficiente de ferro e restrições alimentares para perda de peso, seja pelo estirão do crescimento, pela maturação sexual ou pela menarca, que provoca eliminação de ferro orgânico (Alquaiz et al, 2015;Bird et al, 2017;Mota et al, 2019;Skolmowska & Glabska, 2019;Wirth et al, 2017).…”
Section: Discussionunclassified
“…As condições socioeconômicas e a escolaridade materna são fatores determinantes para a prevalência da anemia em adolescentes, por se associarem ao baixo consumo de alimentos ricos em ferro biodisponível, às condições precárias de saneamento e moradia, e ao maior risco de infecções parasitárias (Bezerra et al, 2018;Mota et al, 2019;Spezia et al, 2018) Esta relação foi encontrada em vários estudos (Prasanth, 2017;Shaka & Wondimagegne, 2018;Thomas et al, 2015). No entanto, a associação da anemia com esses fatores não foi constatada nesta pesquisa, à semelhança de outras publicações (Bezerra et al, 2018;De la Cruz-Góngora et al, 2016).…”
Section: Discussionunclassified